2009
DOI: 10.1111/j.1365-2133.2009.09136.x
|View full text |Cite
|
Sign up to set email alerts
|

TRAF1/C5polymorphism is not associated with pemphigus

Abstract: gene. High prevalence of the carrier state was also observed. We therefore recommend genetic counselling in communities where AE is observed and advocate increased awareness of possible variable phenotypic expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…By contrast, individuals with rs700218 * A (intron 1 of C9 ) were more protected (OR = 0.12; p = 0.0471). We found no association with C5 polymorphisms, as reported by others (who investigated only one SNP) ( 99 ). Nevertheless, individuals with the rs10404456 * C allele (located in the 5′ UTR of the C5AR1 gene and associated with decreased mRNA levels in sun-exposed skin) ( 83 ) presented increased susceptibility to PF (OR = 1.43 p = 0.0155).…”
Section: The Long Known Versus the Unexpected: Complement In Pfsupporting
confidence: 70%
“…By contrast, individuals with rs700218 * A (intron 1 of C9 ) were more protected (OR = 0.12; p = 0.0471). We found no association with C5 polymorphisms, as reported by others (who investigated only one SNP) ( 99 ). Nevertheless, individuals with the rs10404456 * C allele (located in the 5′ UTR of the C5AR1 gene and associated with decreased mRNA levels in sun-exposed skin) ( 83 ) presented increased susceptibility to PF (OR = 1.43 p = 0.0155).…”
Section: The Long Known Versus the Unexpected: Complement In Pfsupporting
confidence: 70%
“…The SNP rs10818488 is an eQTL for different genes and could have a functional impact on C5 synthesis. Even so, this regulatory intergenic SNP was not associated with PF and PV in the Tunisian population (Mejri et al, 2009). In line with this result, C5 polymorphisms were also not associated with FS (Bumiller-Bini et al, 2018).…”
Section: Genetics Sheds Light On the Controversial Relevance Of The Csupporting
confidence: 61%
“…However, while another study showed a positive association of TNFa (À308 G/A) promoter gene polymorphism with sporadic PF [7]. Our previous study showed no significance between the disease and the rs10818488 G/A, located in the intergenic region between the complement C5 and TRAF1 gene ''TNF receptor associated factor'' gene, nor with the C5 sera levels which could strengthen the secondary role of complement in the PF [8].…”
Section: Introductionmentioning
confidence: 58%